The antibacterial activity of palm oil (Elaeis guineensis) leaf extracts against staphylococcus aureus / Nur Fatihah Nordin, Hasnah Begum Said Gulam Khan and Jamil Kazi Ahsan - Nordin, Nur Fatihah; Said Gulam Khan, Hasnah Begum; Ahsan, Jamil Kazi (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Plants offer a rich source of antimicrobial agents and bioactive compounds. In this study, aqueous palm oil leaves extracts (POLE) have been used as an alternative antibacterial agent against oral infections mainly caused by S. aureus. Many previous studies report the potential use of palm oil leaf extracts in treating bacterial infections such as Escherichia coli, Salmonella species, Pseudomonas aeruginosa and Bacillus species. However, few studies have been reported on the effect of palm oil leaves extract on oral microbes. Agar diffusion method, minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) assay were conducted to observe the antibacterial activity of aqueous palm oil leaves extract. The crystal violet assay was used to determine the anti-biofilm activity of the extracts. For agar diffusion method, the diameter of inhibition zone was measured. The inhibition zone of the tested bacteria was observed between 0-20 mm. The MIC and MBC values for the tested bacteria were 3.906 mg/mL and 7.813 mg/mL respectively. While for anti-biofilm assays, aqueous POLE extract acts as a potent anti-biofilm agent with dual actions, preventing and eradicating the biofilm of the tested bacteria. In conclusion, we suggest that the aqueous POLE extract may serve as alternative natural antibacterial and anti-biofilm agent against oral infections.